Fusão em leito de pó a laser de aço ferramenta A2: efeito de parâmetros de processo, tratamentos térmicos e adição de Cr₃C₂ - Bianchini, Bruno (2025)
Tool steels have strict requirements for composition, processing and mechanical properties, and are utilized in fabrication of molds or tools employed in the processing of other materials. In many cases, they are expensive and of difficult machinability, which opens up the possibility for alternative processing routes such as additive manufacturing (AM) by Laser Powder Bed Fusion (L-PBF), which allows fabrication of parts with complex sections, such as internal cooling channels, without additional processing cost and with minimal need for post-processing, due to its great dimensional accuracy. However, the severe conditions to which the L-PBF process submits materials induce the formation of a highly refined microstructure, and possibly defects. This work studies the possibility of manufacturing AISI A2 tool steel by L-PBF, considering the effect of process parameters and post-processing in its microstructure and properties, and the modification of this material for defect mitigation. Results showed that, despite it being possible to determine a processing window for minimal porosity, the material composition and the severe processing conditions cause the formation of cracks, mostly during solidification. The as-built microstructure is, similarly to other tool steels manufactured by L-PBF, composed of martensite cells surrounded by retained austenite, while the formation of primary carbides is suppressed. After heat treatment, the formation of secondary carbides was found to be also in low quantity, showing that temperings without prior austenitization would need higher temperatures or longer times to cause significant effects on the microstructure and mechanical properties. Finally, it was discovered that the addition of Cr3C2 chromium carbide by mechanical mixture, at a fraction of 5%, was capable of mitigating defect formation by altering the alloy composition, when manufactured by L-PBF.